Distribution and Activity of the Plasma Membrane H+-ATPase in Mimosa pudica L. in Relation to Ionic Fluxes and Leaf Movements. - Fleurat-Lessard, P. (1997)
Plasma membrane H+-ATPase was immunolocalized in several cell types of the sensitive plant Mimosa pudica L., and transmembrane potentials were measured on cortical cells. In comparison with the nonspecialized cortical cells of the petiole or stem, the proton pump was highly expressed in motor cells. These immunological data are in close agreement with electrophysiological data, because the active component of the transmembrane potential was low in the nonspecialized cortical cells and high in motor cells. Therefore, motor cells contain the plasma membrane H+-ATPase required to mediate the ionic fluxes that are involved in circadian leaf movements and that are necessary to recover the turgor potential that is considerably affected by the large K+ and Cl- efflux associated with seismonastic movement. With the exception of sieve tubes, the phloem also had a high density of H+-ATPase. This suggests that the recovery of the transmembrane ionic gradients (K+ and Cl-), which is affected by various stimuli, is more energized by the companion and parenchyma cells than by the sieve elements. In addition, at the phloem/cortex interface collocytes displayed the required properties for lateral transduction of the action potential toward the pulvinal motor cells.